Pegaruh Kualitas Pelayan, Kualitas Produk, dan Lokasi Terhadap Kepuasan Pelanggan Piknik Coffee Eatery Purbalingga - Bondan Pradiptasani Suryawan; Arini Hidayah; M. Agung Miftahuddin; Maulida Nurul Innayah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the influence of service quality, product quality, and location on customer satisfaction at Piknik Coffee Eatery Purbalinga. The sample in this study was 110 customers of Piknik Coffee Eatery Purbalingga. This research applies a quantitative approach with a questionnaire as data collection. Purposive sampling was implemented as a sampling technique, with criteria 1). Purbalingga people who have visited Piknik Coffee Eatery at least 2 times and 2). Minimum age 17 years. Multiple linear regression technique using SPSS version 25 software. The results of this research show that Service Quality has no positive and significant effect on customer satisfaction, Product Quality has a positive and significant effect on customer satisfaction, and Location has no effect on customer satisfaction of Piknik Coffee Eatery Purbalinga.